Normal smell identification score and N-butanol threshold in Thai adults - Saisawat Chaiyasate (2018)
Objective: To identify commonly recognized odorants and to find a normal threshold for n-butanol in Thai adults. Material and Method: Eighty-one normal adult volunteers were enrolled between April and September 2010. They were asked to sniff from each glass bottle as long as they preferred. The threshold test was performed in an ascending method. Each volunteer was asked to identify the n-butanol dilution bottle from two bottles of distilled water. Fifteen odorants available as commercial products were used for the identification test. Volunteers had to sniff each bottle and chose the answer from four choices. Results: There were 33 male (40.7%) and 48 female (59.3%) volunteers. The mean age (± standard deviation) was 38.8±11.4 years, ranged from 22 to 60 years. The most common threshold bottle was number nine (40.7%). The most commonly recognized odorant was fish sauce (100%). The most intolerable odorant was ammonia (77.8%). The mean correct identification score (± standard deviation) was 13.6±1.4 odorants, ranged from six to 15 odorants. Conclusion: The present study showed commonly recognized odorants that could be used for an identification test and the normal n-butanol threshold in Thai adults.